Resposta de cultivares de feijoeiro comum à calagem superficial em semeadura direta - Benetoli da Silva, Tiago Roque; Lemos, Leandro Borges [UNESP]; Costa Crusciol, Carlos Alexandre [UNESP]; Fiorentin, Ciro Franco [UNESP] (Universidade Estadual de Londrina (UEL), 2012)
Soil acidity in no tillage system, if not in high situations, can be neutralized by lime surface application, improving mineral nutrition and crop yield. Aiming to evaluate the agronomic performance of common bean cultivars, to surface lime application, in no tillage system, an experiment was conducted in Oxisol, Botucatu Municipal District, São Paulo State, Brazil. The experimental design was a complete randomized block in split plot with four replications, where the plots were formed by common bean cultivars (Carioca, IAC Carioca Ete, Perola, IAPAR 81 e Campeao 2) and subplots consisted of surface application of dolomitic limestone (zero, 1.8 t ha(-1), 3.6 t ha(-1) and 5.4 t ha(-1)). The surface lime application on the soil occurred in October 2002 and subsequently the sequence millet (spring) - beans (summer) - oat (autumn-winter) were planted under rainfed conditions. Bean cultivars sowing were done on December 17, 2003. It can be concluded that there is influence of cultivars and limestone surface application under no tillage, where IAPAR 81 showed better grain yield with the increase of lime rates, obtaining values of 2,025 kg ha(-1) without the lime application to 2,655 kg ha(-1) with 5.4 t ha(-1) lime rate, obtaining 31% yield increase.
Common bean cultivars response to lime surface application under no tillage system
Keywords: Phaseolus vulgaris L.; Soil acidity; Yield